Return to Tradd Street - White, Karen (Karen S.) (New American Library, 2014)
"Melanie is only going through the motions of living since refusing Jack's marriage proposal. She misses him desperately, but her broken heart is the least of her problems. Despite an insistence that she can raise their child alone, Melanie is completely unprepared for motherhood, and she struggles to complete renovations on her house on Tradd Street before the baby arrives. When Melanie is roused one night by the sound of a ghostly infant crying, she chooses to ignore it. She simply does not have the energy to deal with one more crisis. That is, until the remains of a newborn buried in an old christening gown are found hidden in the foundation of her house. As the hauntings on Tradd Street slowly become more violent, Melanie decides to find out what caused the baby's untimely death, uncovering the love, loss, and betrayal that color the house's history--and threaten her claim of ownership. But can she seek Jack's help without risking her heart? For in revealing the secrets of the past, Melanie also awakens the malevolent presence that has tried to keep the truth hidden for decades..."--